(untitled) (Bangladesh Journal of Zoology, 2016)
A study on status and diversity of birds of Ramna Park, Dhaka, Bangladesh was conducted from July 2013 to March 2014. Data were collected through direct field observations where 6 days had been spent in every month in the field. A total of 50 species of birds belonging to 11 orders and 28 families were observed. Of the 50 species, 84% were residents and 16% migrants, 50% were passerines, 50% non-passerines. Passeriformes presented the highest number (25 species) of observed birds. Only Clamator jacobinus was recorded as summer migrant among the migratory birds. We found Psittacula eupatria considered as Near Threatened globally according to IUCN. Corvus splendens was the most common with the highest number of individuals in comparison to other bird species. We observed single individual of Clamator jacobinus followed by Psittacula eupatria and Apus pacificus throughout the study. Regarding the relative abundance, 18% species were very common, 30% common, 16% fairly common and 36% few. Calculating the Shannon-Wiener and Simpsons indices of diversity and species evenness, we found maximum number of species and individuals in the month of December while minimum in the month of July. Anthropogenic activities such as festivals, random assemblies and gatherings, dumping of plastics, polythene and papers, noise from the vehicles were common inside and around the park, which may be threats to birds. Bangladesh J. Zool. 43(2): 291-301, 2015